(untitled) (KONFERENSIYA, 2025)
This article examines the impact of Artificial Intelligence (AI) on the development of oral communication skills among non-philology university students. While learners in non-linguistic fields often experience limited exposure to English speaking practice, AI-powered tools provide flexible, personalized, and interactive learning environments. The study discusses theoretical foundations, types of AI utilized in oral communication training, practical classroom applications, pedagogical benefits, challenges, and future prospects. Findings indicate that AI significantly contributes to the enhancement of pronunciation accuracy, fluency, vocabulary use, confidence, and overall communicative competence. The article concludes with recommendations for integrating AI into EFL speaking instruction for diverse academic majors